The invasive potential of a hybrid species: insights from soil chemical properties and soil microbial communities. (15th November 2019) - Sun, Feng; Ou, Yuyi; Ou, Qiaojing; Zeng, Lingda; Yu, Hanxia; Zheng, Jin; Gao, Lei; Li, Weihua; Li, Na; Peng, Changlian
Abstract: Aims: Natural hybridization between invasive and native species, as a form of adaptive evolution, threatens biodiversity worldwide. However, the potential invasive mechanisms of hybrids remain essentially unexplored, especially insights from soil chemical properties and soil microbial communities. Methods: In a field experiment, soil microbial community, potassium-solubilizing bacteria, phosphorus-solubilizing bacteria, enzyme activities, and light-saturated photosynthetic rate were measured in invasive Sphagneticola trilobata and its hybrid with native Sphagneticola calendulacea in 2 years. Important Findings: In general, soil dissolved organic carbon and the biomass of phosphorus-solubilizing bacteria were significantly higher under the hybrid treatment than S. trilobata and S. calendulacea . However, there were no significant differences in acid phosphatase, total PLFAs, bacterial PLFAs, fungi PLFAs, cellulase, and urase in these treatments. The hybrids had significantly higher light-saturated photosynthetic rate, photosynthetic nitrogen-, phosphorus-, potassium- use efficiencies than the invasive S. trilobata, but no significant difference with S. calendulacea . The total biomass and root biomass of hybrids were higher than S. calendulacea. Our results indicate that the hybrids species have a higher invasive potential than S. calendulacea, which may aggravate the local extinction of S. calendulacea in the future.